Designing a survey to examine an anonymisation method for driver videos - Jansson, Marcus (My University, 2011)
Data collected during naturalistic driving studies often includes video of the driver’s face. Due to the Data Privacy Act (“Personuppgiftslagen” (PuL) in Swedish), it is desirable to find a good method that can make the driver’s face anonymous, while keeping the original driver‘s facial expressions. In the unEye project, an attempt to create such method was made. Using this method, the original driver’s facial expressions are coded into action units which are then used to construct a corresponding video in which the driver face is replaced by an animated face model. This thesis project was conducted to validate whether the anonymisation method built in the unEye project could really achieve its objectives. In particular, this thesis contributes in validating whether a human viewer can identify who the original driver was from the animated version of the video and examining how well the facial expressions are translated when creating the animated driver videos. For this, a computer-based survey was designed and performed. The survey has two different parts corresponding to the two different validation tasks. The results from the survey showed some unexpectedly high number of correct classifications in the identification part. However, some explanations were found which suggest that these high numbers were most likely due to other reasons than the ability of the test participants to identify the driver. For the expressions part, the result showed that surprise was the best preserved expression and that anger was the most poorly preserved one. The average recognition proportion of the expressions was 24% and some patterns were found in the results which indicate that the details in the face are not translated well enough, especially in the regions around the mouth, eyes and eyebrows. In conclusion, while the method is able to make the driver face anonymous, it should be improved so that the facial expressions are better translated. The results were also examined with respect to the age, gender, area of occupation and education level of the test participants and no clear difference could be found within these groups. This indicates that the result could be generalised to a larger population.
Keywords: Transport; Övrig teknisk mekanik; Transport; Other engineering mechanics